The susceptibility of Streptococcus mutans to antibacterial photodynamic therapy: a comparison of two different photosensitizers and light sources - Neda HAKIMIHA; Farzaneh KHOEI; Abbas BAHADOR; Reza FEKRAZAD (University of São Paulo, 2014)
Streptococcus mutans is the main etiological agent for dental caries. Recently, photodynamic therapy (PDT) has been introduced as a new modality in bacterial decontamination. Objective: This in vitro study was carried out to evaluate the susceptibility of Streptococcus mutans to antibacterial PDT using two different photosensitizers and light sources. Material and Methods: Standard suspensions of S. mutans were exposed to laser light at 662 nm and Radachlorin® or LED 630 nm in combination with Toluidine blue O (TBO). Radiation-only groups, photosensitizer alone, and groups with no treatment were used as controls. Bacterial suspension from each treatment was subcultured onto the surface of Mueller-Hinton agar plates and bacterial growth was assessed. The results were analyzed by analysis of variance and Tukey test (p<0.05). Results: PDT with TBO and Radachlorin® significantly reduced S. mutans viability, whereas no difference was observed between two groups of PDT. In the groups treated just with the photosensitizer or irradiated alone, no significant reduction of S. mutans colonies was observed. Conclusion: S. mutans colonies were susceptible to either 662 nm laser or LED light in the presence of Radachlorin® and TBO respectively with no priority.